Cleft lip repair: are outcomes between unilateral and bilateral clefts comparable?. Issue 1 (2nd January 2020) - Chouairi, Fouad; Mets, Elbert J.; Torabi, Sina J.; Alperovich, Michael
Abstract: This study sought to compare patient demographics, operative course, and peri-operative outcomes between unilateral and bilateral cleft patients. Primary cleft lip repairs were isolated from the National Surgical Quality Improvement Program Pediatric Database (NSQIP-P). Unilateral and bilateral cases of primary cleft lip were identified by ICD codes. Demographics, comorbidities, and post-operative outcomes were compared between cohorts. Patients were propensity matched to control for differences before repeating the analysis. About 4550 cleft lip repairs were evaluated over the 5-year period. Of the cases where the cleft type was identifiable, 75.5% were unilateral clefts and 24.5% were bilateral clefts. The bilateral cleft population had significantly more comorbidities including higher rates of ventilator dependence (1.0% versus 0.4%, p  = 0.02), asthma (1.6% versus 0.7%, p  = 0.011), tracheostomy (1.6% versus 0.5%, p  < 0.001), gastrointestinal disease (16.9% versus 12.7%, p  < 0.001), previous cardiac surgery (3.6% versus 2.2%, p  = 0.015), developmental delay (9.9% versus 4.6%, p  < 0.001), structural central nervous system abnormalities (5.0% versus 2.5%, p  < 0.001), and nutritional support (8.0% versus 3.2%, p  < 0.001). Following propensity matching, there were no significant differences in complications, readmissions, or reoperations between the cohorts. Patients with bilateral cleft lip have significantly more comorbidities than unilateral cleft lip patients. However, peri-operative outcomes are comparable between the groups.